Catalytic reduction of N2O with CH4 over various Cu-SBA-15 catalysts - M. H. M., Husin; M. R., Nordin; I. S., Mohamad; S. Y., Chin (Centre for Advanced Research on Energy, 2018)
The N2O catalytic reduction by methane over Cu-SBA -15 molar ratio (1:30) was studied based on physical mixture, impregnation method and pH adjustment method preparation. All catalytic reduction of N2O with methane were carried out in a flow reactor system at atmospheric pressure with 100 mL/min total flow was used. For the N2O:CH4 ratio effect, suggested that N2O reacts with CH4 is represented by 4N2O + CH4  4N2 + CO2 + 2H2O. The Cu/SBA-15 prepared by pH adjustment method has highest activity compared to Cu-SBA-15 prepared by impregnation method and physical mixture of CuO and SBA-15.